2010
DOI: 10.1002/syn.20780
|View full text |Cite
|
Sign up to set email alerts
|

Fenfluramine‐induced serotonin release decreases [11C]AZ10419369 binding to 5‐HT1B‐receptors in the primate brain

Abstract: The need for positron emission tomography (PET)-radioligands that are sensitive to changes in endogenous serotonin (5-HT) levels in brain is recognized in experimental and clinical psychiatric research. We recently developed the novel PET radioligand [(11)C]AZ10419369 that is highly selective for the 5-HT(1B) receptor. In this PET-study in three cynomolgus monkeys, we examined the sensitivity of [(11)C]AZ10419369 to altered endogenous 5-HT levels. Fenfluramine-induced 5-HT release decreased radioligand binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 296 publications
(380 reference statements)
4
42
0
Order By: Relevance
“…The here reported mean fenfluramine effect on [ 11 C]AZ10419369 binding across eight brain regions (À12% at 1.0 mg/kg; À33% and À34% at 5.0 mg/kg) is in line with our previous study, in which [ 11 C]AZ10419369 was administered as a bolus injection (À27% at 1.0 mg/kg; À50% at 5.0 mg/kg; Finnema et al, 2010). A comparable effect of fenfluramine on radioligand binding has more recently also been showed using the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al, 2010) and the 5-HT 1B receptor radioligand […”
Section: Discussionsupporting
confidence: 92%
“…The here reported mean fenfluramine effect on [ 11 C]AZ10419369 binding across eight brain regions (À12% at 1.0 mg/kg; À33% and À34% at 5.0 mg/kg) is in line with our previous study, in which [ 11 C]AZ10419369 was administered as a bolus injection (À27% at 1.0 mg/kg; À50% at 5.0 mg/kg; Finnema et al, 2010). A comparable effect of fenfluramine on radioligand binding has more recently also been showed using the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al, 2010) and the 5-HT 1B receptor radioligand […”
Section: Discussionsupporting
confidence: 92%
“…It may therefore be assumed that elevation in 5-HT levels in response to AZD3783 administration may reduce radioligand binding to brain 5-HT 1B receptors. Sensitivity of [ 11 C]AZ10419369 to changes in endogenous 5-HT has indeed been previously demonstrated by fenfluramine challenge in monkeys (Finnema et al 2010). Therefore, it cannot be excluded that occupancy values measured in the present study result from a combination of AZD3783 Fig.…”
Section: Discussionsupporting
confidence: 57%
“…We previously demonstrated that the potent serotonin releaser fenfluramine reduced the binding of the 5-HT 1B receptor radioligand [ 11 C]AZ10419369 in non-human primates by up to 50 % (Finnema et al 2010(Finnema et al , 2012, and similar results have been reported by others using the 5-HT 1B receptor radioligand [ 11 C]P943 (Cosgrove et al 2011;Ridler et al 2011) or the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al 2011). The effects of single SSRI doses have also been evaluated in anaesthetized non-human primates (NHPs) in preparation for studies in human.…”
Section: Introductionmentioning
confidence: 99%